Integral Representation of Functions and Embedding Theorems for Multianisotropic Spaces in the Three-Dimensional Case - Karapetyan, Garnik (Eurasian Mathematical Journal, 2016)
In this paper we obtain a special integral representation of functions with a set of multi-indices and use it to prove embedding theorems for multianisotropic spaces in three-dimensional case.